Conspicuous Consumption and its Relation to Brand Consciousness, Status Consumption and Self-Expression - Bruno Medeiros Assimos; Marcelo de Rezende Pinto; Ramon Silva Leite; Matheus Lemos de Andrade (BBR: Brazilian Business Review)
This paper presents and discusses the results of an empirical research whose objective was to discuss the relationship between the concepts of conspicuous consumption, status consumption and self-expression. For this, we have used the model proposed by Mann and Sahni (2015), which suggests the existence of three fundamental dimensions in the explanation of conspicuous consumption, setting the discussion under the aegis of lifestyle, brand consciousness, consumption of status and self-expression. An online survey was implemented, which generated a database composed of 398 respondents who had attended a marriage ceremony in the last six months. For data analysis, the modeling of structural equations using the PLS approach was used. The results of the study suggest, among other findings, that there is a relatively strong association between the constructs status consumption and self-expression, it was also possible to verify a significant and positive influence between the dimensions of the construct conspicuous consumption with status consumption. In addition, we found that there is a strong influence between social conformity and status consumption and between status consumption and self-expression. Thus, the article contributes to the studies of consumption by advancing the discussion about the antecedents and consequences of conspicuous consumption and the relationship between conspicuity and status.